Exploring the nematicidal mechanisms and control efficiencies of oxalic acid producing Aspergillus tubingensis WF01 against root-knot nematodes - Yang, Zhong-Yan; Dai, Yuan-Chen; Mo, Yuan-Qi; Wang, Jia-Lun; Ma, Li; Zhao, Pei-Ji; Huang, Ying; Wang, Rui-Bin; Li, Wei; Al-Rejaie, Salim S.; Liu, Jian-Jin; Cao, Yi; et al. (Frontiers in Microbiology, 2024)
Background and aims Root-knot nematodes (RKN; Meloidogyne spp.) are among the highly prevalent and significantly detrimental pathogens that cause severe economic and yield losses in crops. Currently, control of RKN primarily relies on the application of chemical nematicides but it has environmental and public health concerns, which open new doors for alternative methods in the form of biological control. Methods In this study, we investigated the nematicidal and attractive activities of an endophytic strain WF01 against Meloidogyne incognita in concentration-dependent experiments. The active nematicidal metabolite was extracted in the WF01 crude extract through the Sephadex column, and its structure was identified by nuclear magnetic resonance and mass spectrometry data. Results The strain WF01 was identified as Aspergillus tubingensis based on morphological and molecular characteristics. The nematicidal and attractive metabolite of A. tubingensis WF01 was identified as oxalic acid (OA), which showed solid nematicidal activity against M. incognita, having LC50 of 27.48 μg ml–1. The Nsy-1 of AWC and Odr-7 of AWA were the primary neuron genes for Caenorhabditis elegans to detect OA. Under greenhouse, WF01 broth and 200 μg ml–1 OA could effectively suppress the disease caused by M. incognita on tomatoes respectively with control efficiency (CE) of 62.5% and 70.83%, and promote plant growth. In the field, WF01-WP and 8% OA-WP formulations showed moderate CEs of 51.25%–61.47% against RKN in tomato and tobacco. The combined application of WF01 and OA resulted in excellent CEs of 66.83% and 69.34% toward RKN in tomato and tobacco, respectively. Furthermore, the application of WF01 broth or OA significantly suppressed the infection of J2s in tomatoes by upregulating the expression levels of the genes (PAL, C4H, HCT, and F5H) related to lignin synthesis, and strengthened root lignification. Conclusion Altogether, our results demonstrated that A. tubingensis WF01 exhibited multiple weapons to control RKN mediated by producing OA to lure and kill RKN in a concentration-dependent manner and strengthen root lignification. This fungus could serve as an environmental bio-nematicide for managing the diseases caused by RKN.